Тенденции развития экономики украины в условиях современного рынка трудовых ресурсов - Садовский, Виктор Артемович; Семенченко, Галина Владимировна; Подхалюзин, Андрей Юрьевич (НТУ "ХПИ", 2018)
В статье исследованы значение, основные виды, социально-экономические причины и места трудовой миграции в Украине. Приведены статистические данные, а также предложены возможные пути решения проблемы международной миграции в стране. Раскрыты основные факторы сокращения трудовых ресурсов в стране. Проанализирован уровень, выявлены основные проблемы и последствия молодежной безработицы в Украине. Показан экономический ущерб от миграционной политики государства.

The statute has the most significant, basic, socially economical reasons and the employment of the migrant in Ukraine. Statistical data has been given, and also, you can meet the chances of international problems in the country. The main principles of the labor resources are in the country. An analysis has been made of the issue, the main outbreaks of problems and problems of young people in Ukraine. Indications are economical cases of intern ational policy. Set out proposals to reduce labor emigration from Ukraine and stabilize the country's economic potential.
Trends of development of Ukrainian economy in the conditions of modern labor resources market
Keywords: трудовая миграция; безработица; рождаемость населения; смертность населения; социальная нагрузка общества; пенсионная нагрузка общества; labor migration; worklessness